Following the "tracks of righteousness" of Psalm 23 - Botha, Phil J. (Old Testament essays, 2015)
This article argues that possible connections between Ps 23 and Proverbs have been overlooked to a large extent. It is well-known that the author of the psalm has appropriated the image of Yahweh as a shepherd of his people (used in connection with the exodus and also at the return from exile) and applied it to his personal relationship with Yahweh. But the psalm also describes the life of the individual worshipper as a journey and this metaphor seems to have important connections with Proverbs and wisdom psalms. It is argued that the expression "tracks of righteousness" possibly display sa direct link to Prov 2 : 9 and 4 : 11 and that this could imply that the author of Ps 23 fused the metaphor of Yahweh as a shepherd (and as a host) with that of Yahweh as a guide on the road of life so that the suppliant is portrayed as a righteous person.,